Increased plasma/serum levels of prolactin in systemic lupus erythematosus: a systematic review and meta-analysis. Issue 1 (2nd January 2017) - Wang, Peng; Lv, Tian-Tian; Guan, Shi-Yang; Li, Hong-Miao; Leng, Rui-Xue; Zou, Yan-Feng; Pan, Hai-Feng
ABSTRACT: Background: Prolactin (PRL), a polypeptide hormone produced by the pituitary gland, is involved in the regulation of humoral and cell mediated immune responses. PRL levels have been investigated in several autoimmune diseases including systemic lupus erythematosus (SLE), however, yielded different and inconsistent results. This study aims to derive a more precise evaluation on plasma/serum PRL levels in SLE patients, as well as the potential influential factors. Methods: Studies published from 1 January 1987 to 31 December 2015 in English, which comparing plasma/serum PRL levels between SLE group and control group were searched in PubMed, EMBASE and The Cochrane Library databases. Pooled standard mean difference (SMD) with 95% confidence interval (CI) was calculated by fixed-effects or random-effect model analysis. Heterogeneity test was performed by the Q statistic and quantified using I 2, publication bias was evaluated using a funnel plot and Egger's linear regression test. Results: Five-hundred and forty-seven articles were obtained after searching databases, and 12 studies with 429 SLE patients and 326 controls were finally included. Meta-analysis revealed that, compared with the control group, the SLE group had significantly higher plasma/serum PRL levels ( P < 0.001), with the SMD of 1.26 and 95%CI (0.70，1.82). Subgroup analyses showed that SLE patients from Asia and Europe had higher plasma/serum PRL levels. However, no significant change in plasma/serum PRL levels was observed in SLE patients from America ( P > 0.05). Conclusions: Overall, our study suggests that SLE patients have higher plasma/serum PRL level, but with a regional difference.